Analysis of Work-Life Balance and its Impact on Employee Performance in the Office of the Governor of North Sumatra - Sari Wulandari; Nirma Yunita Siregar; Nur Hazizah; Sucitra Putri; Syarianda Syafitri (Jurnal Bisnis dan Manajemen (JURBISMAN), 2025)
This study aims to analyze the effect of work-life balance on employee performance in the North Sumatra governor's office. In the modern work era, high work pressure often leads to an imbalance between personal and professional life, which has the potential to reduce productivity and job satisfaction. This research uses a descriptive-analytical approach that aims to describe in depth the condition of work-life balance and analyze its impact on employee performance in the Office of the Governor of North Sumatra. Employees who feel they have a good balance tend to show higher performance, be more loyal, and more satisfied with their work. This provides implications for human resource management in the government environment to pay attention to work balance as a strategy to improve organizational performance